2012
DOI: 10.4172/2155-6113.1000138
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical and First-In-Human Phase I Clinical Evaluation of Stampidine, a Potent Anti-HIV Pharmaceutical Drug Candidate

Abstract: The rationally designed novel anti-HIV drug candidate Stampidine exhibited (a) remarkable subnanomolar to low nanomolar in vitro ARV potency against genotypically and phenotypically NRTI-resistant primary clinical HIV isolates, non-nucleoside reverse transcriptase inhibitor (NNRTI)-resistant HIV-1 isolates, clinical non-B subtype HIV-1 isolates (subtypes A, C, F, and G) originating from South America, Asia, and sub-Saharan Africa with resistance to stavudine, adefovir and tenofovir, as well as recombinant HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Results from these studies involving oral dosing of stampidine did not show any dose-limiting toxicity at single dose levels of up to 25 mg/kg. 39 Beyond its potential in treating HIV-resistant strains, stampidine was also suggested as a promising candidate in the pre-exposure prophylaxis against HIV in heterosexual women as well as serodiscordant couples. 40 Thymectacin 35 is a phenyl L-alanine methyl ester ProTide of the therapeutic nucleoside brivudine (BVdU), which is used to treat herpes zoster (shingles).…”
Section: Stampidine and Thymectacinmentioning
confidence: 99%
“…Results from these studies involving oral dosing of stampidine did not show any dose-limiting toxicity at single dose levels of up to 25 mg/kg. 39 Beyond its potential in treating HIV-resistant strains, stampidine was also suggested as a promising candidate in the pre-exposure prophylaxis against HIV in heterosexual women as well as serodiscordant couples. 40 Thymectacin 35 is a phenyl L-alanine methyl ester ProTide of the therapeutic nucleoside brivudine (BVdU), which is used to treat herpes zoster (shingles).…”
Section: Stampidine and Thymectacinmentioning
confidence: 99%
“…Adding up, TFV modulation of proinflammatory cytokines (TNF-α, IL-2, IL-7, and IL-12p70) and activation of natural killer cells were associated with HIV-1 acquisition in women showing high systemic innate immune activation before infection. 41 Aside from TFV, a distinct new HIV anti-retroviral, stampidine, was evaluated recently in phase I clinical trial, and showed no toxicity at dosage ranging from 5 to 25 mg kg − 1 when taken daily as capsules, 42 which offers an alternative option of using anti-retrovirals as microbicide strategy. To overcome barriers to adherence, intravaginal ring (IVR 25 mg or IVR 200 mg) formulated with a non-nucleoside RT inhibitor (Dapivirine) has been developed.…”
Section: Non-anti-retroviral Based Microbicide Candidatesmentioning
confidence: 99%
“…Stampidine is a promising ARV drug candidate against HIV because of (a) its remarkable subnanomolar to low nanomolar in vitro anti-retroviral potency against genotypically and phenotypically NRTI-resistant primary clinical HIV isolates, non-nucleoside reverse transcriptase inhibitor (NNRTI)-resistant HIV-1 isolates, as well as clinical non-B subtype HIV-1 isolates (subtypes A, C, F, and G) originating from South America, Asia, and sub-Saharan Africa with resistance to stavudine, adefovir and tenofovir [28], (b) favorable pharmacokinetics profile in rodents, dogs, and cats with 25 mg/kg or 50 mg/kg tolerable dose levels yielding micromolar plasma concentrations of Stampidine in rodents, cats, and dogs, which are 1,000-fold higher than its in vitro IC 50 value against HIV [29,30], (c) favorable, safety profile in rodents, dogs, and cats [29,30], and (d) in vivo anti-retroviral activity in Hu-PBL-SCID mice as well as FIV-infected domestic cats [31]. In a recently completed placebo-controlled Phase I study involving 30 therapy-naïve adult HIV-infected adult patients, formulated cGMPgrade Stampidine [32] administered as a single oral bolus dose did not cause dose-limiting toxicity at single dose levels ranging from 5 to 25 mg/kg, but it resulted in modest decreases in HIV load in 9 patients [33]. The favorable preclinical and early clinical safety/activity profile of Stampidine warrants its further development as a new anti-HIV drug candidate against ARV drug-resistant HIV strains.…”
Section: Stampidine Causes Methylation Of a Subset Of Hiv-responsive mentioning
confidence: 99%